PENANAMAN SIKAP PRO-LINGKUNGAN MELALUI PENGEMBANGAN DESA WISATA “KAMPOENG KALEN” DI DUSUN DANEN - Ayu Rahayu; eko yuliyanto (Pendidikan Kimia Unimus, 2018)
Danen is located in Sumberadi village, Mlati sub-district, Sleman district, Daerah Istimewa Yogyakarta (DIY) Province. This hamlet has the potential of good natural resources and human resources especially active youth. However, this potential is not balanced with the attitude of people who are less concerned about the environment (pro-environment). The presence of littering and degradation of watersheds is a form of the necessity of planting a pro-environment attitude of the community. The development of tourist village